Eurasian Economic Union integrates energy markets: EU stands aside - Maria Pastukhova; Kirsten Westphal (Stiftung Wissenschaft und Politik (SWP), 2018)
The process of establishing a common energy market in the Eurasian Economic Union (EAEU) is moving forward after Russia and Belarus succeeded in resolving important differences. This reorganisation of the energy space will also affect the European Union, because Russia and Kazakhstan are major oil and gas suppliers, and important export pipelines originate there. At the same time regulatory and technical fault lines are becoming apparent between the EU/European Energy Community and the EAWU - also affecting transnational physical infrastructure. Furthermore, the integration blocs overlap in sensitive regions like the Caucasus, the Black Sea region and the Baltic states.
Keywords: 320